al-Mustajiddat al-fikriyah fi nizam hukm al-khilafah al-rashidah Abu Bakr al-Siddiq wa-'Umar ibn al-Khattab namudhajan = Intellectual innovation in the ruling system of the righty guided caliphate : a case study of Abu Bakar al-Siddiq and U'mar bin al-Khattab / Kasem K.H.S. alGanabi - Alganabi, Kasem K.H.S. (2013)
The study deals with the two intellectual innovations in the guided caliphate of the Abu Bakar al-Siddiq and U'mar in Al-Khattab which is an extension for the prophet's government (peace be upon him) and to which the prophet helalded his companions before his death. The prophet also talked about the era that will bring back the nation to the guided caliphate approach which will correct the intellectual innovations that piled up during centuries and will occur in future. As for Al-Siddiq and Al-Faroq caliphate innovations unanimitly considered as the third source after the holy Qur'an and Al-Suna. The three sources have the dignity among all Muslims. The companions chose Al-Siddiq to be the first caliphate in the rule not prophecy during the first hours of the prophet death and even before his burial to chose the first caliphate to the Islamic nation on conditional allegiance to apply Islamic rules according to Al-Sharee'a in the decisiveness and undecisiveness matters and cancelling decisions if it does not agrees with Al-Sharee'a. while Al-Ijtihad was on the measuring basis for what Al-Igtihad permits in the new cases, and it is a necessary and fixed in the Isulieen. The two caliphates are central in appointing and dismissal, in adopting the Sultanic rules, foreign affairs such as declaring war, peace treaty contracting, and interior policy such as monetary affairs, interior problems and observance he people interests in the whole nation. Caliphate al-Faroq and Al-Sadeeq do Igtihad to have consensus on what is worked hard (Igtuhida), and often Yagtahid and have a little mistake and correct it immediately when one of the companions miss the definitive text of the caliphate significance recedes worked hard for what Igtuhida in it. Both caliphates were Yagtahidun with agreement and often Yagtahid and get right of a little wrong and it is corrected by one of the companions immediately when thee caliphate miss a decision and to cancel in what he Igtahada in it. Both caliphate were obeyed in the rule and judged when miss judging unintentionally, with the balance between the obedient and the ruler, the regime becomes right.The one studies this era to the method of induction, analysis and comparison finds himself living among the leaders of the owners of the doctrine (the principle), give rise to man's relationship with Allah and himself and to other did not give up some of them, and they carried away all of Islam doctrine, worship, ethics and the system of life, they built what carried the civilization Links was able to fall down and open the two civilizations -the Romans and Persians -at the same time and eliminated the strife at home that are not inevitable, and derive evidence of fixed solutions for all an update on them from the cataclysms, abandoning us a wealth of thought went back to him who Atbauhm charitably, and who wants to get out on the empowerment of the Muslims and the perfection of Islam and the unity of Muslims he wanted to find the truth in the form of that era-Rashed, who, Allah bless them and they with him, and pride of the Muslims will return again by the will of Allah, and Allah on a loved one. In the thesis introduction, I insert the reasons for the choice of title, the importance of research, research problem, research objectives, research, questions, research methodology, limitations of the study and literature review.